The management of dental anxiety and impact of psychosomatic factors on dentistry: is recent scientific research translated into German dental practices? - Diercke, Katja; Bürger, Gila Dorothee; Lorenzo Bermejo, Justo; Lux, Christopher J.; Brunner, Monika (Journal of health psychology, 2013)
This study investigated the dentists’ knowledge about psychosomatic medicine. Anxiolytic techniques, considerations about psychosomatic medicine, and referrals to psychotherapists were examined by a questionnaire. Overall, 65 percent felt negatively affected by patients with dental fear. Few dentists used relaxation techniques and hypnosis. The relationship between psychosomatic factors and pain perception was well known, but not their impact on wound healing. The frequency of continuing education courses correlated with a broader range of treatment techniques and less difficulties in treatment. Research evidence about the impact of psychological factors on dental treatment has not been translated into dental practice.